2016
DOI: 10.3389/fneur.2016.00185
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in ABCA1 Gene Causing Tangier Disease in an Italian Family with Uncommon Neurological Presentation

Abstract: Tangier disease is an autosomal recessive disorder characterized by severe reduction in high-density lipoprotein cholesterol and peripheral lipid storage. We describe a family with c.5094C > A p.Tyr1698* mutation in the ABCA1 gene, clinically characterized by syringomyelic-like anesthesia, demyelinating multineuropathy, and reduction in intraepidermal small fibers innervation. In the proband patient, cardiac involvement determined a myocardial infarction; lipid storage was demonstrated in gut, cornea, and aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…However, the mechanisms of peripheral neuropathy in TD are still unclear . Demyelinating findings in electrophysiologic studies are recognized in TD neuropathy . In our analysis, we found that nerve conduction abnormalities were more prominent in the upper extremities than in the lower extremities, and the sural‐sparing pattern was rather frequent as similar as CIDP.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, the mechanisms of peripheral neuropathy in TD are still unclear . Demyelinating findings in electrophysiologic studies are recognized in TD neuropathy . In our analysis, we found that nerve conduction abnormalities were more prominent in the upper extremities than in the lower extremities, and the sural‐sparing pattern was rather frequent as similar as CIDP.…”
Section: Discussionmentioning
confidence: 61%
“…33,49 Demyelinating findings in electrophysiologic studies are recognized in TD neuropathy. 15,36,44,59 In our analysis, we found that nerve conduction abnormalities were more prominent in the upper extremities than in the lower extremities, and the sural- Unkn.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The Medical Research Council (MRC) scale was used to measure muscle strength. The detailed family pedigree is displayed in the previously mentioned publication . High‐density lipoprotein levels were nondetectable in patients 1 and 2, and 44 mg/dl (normal >45 mg/dl) in patient 3.…”
Section: Methodsmentioning
confidence: 99%
“…Although neurological involvement in TD is widely heterogeneous, 3 different, often overlapping, phenotypes, have been reported: (a) mononeuritis multiplex with upper limb predominance and frequent facial involvement, in which both axonal and demyelinating features have been described; (b) syringomyelia‐like syndrome, with non–length‐dependent loss of small fibers; and (c) widespread nerve involvement with diffuse axonal loss . Recently, an Italian TD family, carrying a novel Y1698X nonsense mutation in ABCA1 , has been reported . Nerve high‐resolution ultrasound (HRUS) is a noninvasive inexpensive tool for evaluating peripheral nerve morphology that has been applied in acquired and inherited neuropathies .…”
mentioning
confidence: 99%